Effectiveness of Sleep‐Based Interventions for Children with Autism Spectrum Disorder: A Meta‐Synthesis. Issue 5 (May 2017) - Cuomo, Belinda M.; Vaz, Sharmila; Lee, Elinda Ai Lim; Thompson, Craig; Rogerson, Jessica M.; Falkmer, Torbjorn
Abstract : Sleep problems are common in children with autism spectrum disorder (ASD). This meta‐synthesis collated eight previously published systematic reviews examining the efficacy of sleep interventions in children with ASD in an attempt to present a clear analysis of trialed interventions. The collated reviews consider five major groups of sleep interventions for children with ASD: melatonin therapy, pharmacologic treatments other than melatonin, behavioral interventions, parent education/education programs, and alternative therapies (massage therapy, aromatherapy, and multivitamin and iron supplementation). These eight reviews were based on 38 original studies and address the efficacy of interventions across 17 sleep problem domains. The results of this meta‐synthesis suggest that no single intervention is effective across all sleep problems in children with ASD. However, melatonin, behavioral interventions, and parent education/education program interventions appear the most effective at ameliorating multiple domains of sleep problems compared with other interventions. Due to the heterogeneous causative factors and presentations of disordered sleep, further research into the effectiveness of sleep interventions may target specific phenotypic subgroups rather than a broad analysis across the general ASD population. Similarly, future research needs to consider the efficacy of different polytherapeutic approaches in order to provide clinicians with evidence to inform best practice. In the meantime, this review supports clinicians' decision making for a majority of the identified sleep problems in the ASD population.